The orientation of social codes within the context of primary socialization - implications for school success/failure - Neves , Isabel (2025)
The orientation of social codes in the family, although determined by sociological factors (social class, race, sex, participation in cultural resistance and reproduction bodies), is in itself one of the principles which characterize the context of primary socialization and which can explain success or failure in school. The study is based on Bernstein's theory of pedagogical discourse and focused on a sample of 80 socially differentiated pupils (social class, race, sex) from a preparatory school in the Lisbon periphery. The orientation of social codes was measured by means of an instrument consisting of scientific and social terms. Four possible definitions were presented for each of those terms, differentiated in accordance with two dimensions (concrete/abstract and implicit/explicit), which indicated a particularist/universalist orientation. The pupils' parents were asked to choose the most appropriate definition. The results obtained were related to achievement in science, in the simple and complex cognitive skills. In order to appreciate the influence of the pedagogical context of the school, we considered, in the relation established the initial achievement (1st term of the 5th grade) and the final achievement (3rd term of the 6th grade). The research carried out suggests that the orientation of the social codes of the family influences the pupils' success, particularly as regards complex cognitive skills. It further suggests that the school influences the weakening of relations between pupils coming from different socio-cultural environments. These aspects should be considered in the training of teachers.